Appraisal the Key Factors of SCQM using a Combined Approach of SWARA-FISM - Mehdi Ajalli; Mohammad Mahdi Mozaffari (International Journal of Supply Chain Management, 2018)
Researchers in recent years have introduced supply chain quality management as a new concept and use it considered as the last step in the move toward "total quality management" whereby company will be able to increase their quality and competitive advantage by efficiently and effectively integrate of the concepts of "Total Quality Management (TQM)" and "supply chain management (SCM)". In order to achieve this goal in the ABZARSAZI Industry, the first step in the implementation of supply chain quality management, is identifying the key success factors of quality management at the supply chain level; because the failure of this project seems imminent if the chain members do not agree on these factors. For this purpose, in this paper presented a conceptual model of supply chain quality management after the extensive review of the literature and identify the factors that affecting SCQM. Then, given the importance and sensitivity of each factors of proposed model to implement in the ABZARSAZI industry, by using SWARA (Stepwise weight assessment ratio analysis) technique, the final weight of was calculated and ranked in order of importance. The final result of SWARA technique and expert opinions in assessing the factors of SCQM systems in the industry showed that Quality Strategies in Supply Chain were detected in the first rank as the most important factor, and Process Approach was detected in the lowest rank. In following, the relationship and sequence of factors were determined with Fuzzy Interpretive Structural Modelling (FISM). The final result of FISM approach showed that the factors are levelled in five levels. So that Supply Chain Quality Information Systems and Quality Strategies in Supply Chain placed in the first level. Such Process Approach placed in the fifth level. With regard to the proposed model and taken prioritize, an action plan was provided for successful implementation SCQM in the ABZARSAZI industry.